POTENSI KOTA MAKASSAR SEBAGAI KOTA WISATA KULINER MENUJU MAKASSAR KOTA KREATIF - Jariyah, Ainun; Sahabuddin, Romansyah; Rakib, Muhammad; Najamuddin, Najamuddin (Unitri Press, 2024)
This study aims to determine what culinary potentials can be developed in supporting the city of Makassar as a culinary tourism city, the obstacles in developing culinary tourism, and the role of culinary tourism in supporting the city of Makassar towards a creative city. This research is a qualitative descriptive research using observation, interview and documentation data collection techniques. The data analysis technique used is descriptive qualitative analysis in the form of data reduction, data presentation and conclusion. The results showed that the potential of the city of Makassar to become a culinary tourism city includes culinary development that represents Makassar's character, the development of traditional culinary/restaurant communities, the use of local raw materials and unique cooking techniques by culinary entrepreneurs, the availability of traditional food markets and industries, the tradition of organizing culinary promotion activities, culinary centers, and educational centers specializing in creative fields. Obstacles include low standards of human resource management and service to consumers, inadequate facilities and infrastructure, and an unhealthy business climate. The role of culinary tourism in supporting the city of Makassar to become a creative city is as the main engine for the creative industry in the culinary sector and the spearhead of the development of the creative economy so that it can accelerate the achievements of the National Economic Recovery program.